2019
DOI: 10.1002/fsh.10190
|View full text |Cite
|
Sign up to set email alerts
|

How Can We Understand Freshwater Soundscapes Without Fish Sound Descriptions?

Abstract: The ecological importance of the freshwater soundscape is just beginning to be recognized by society. Scientists are beginning to apply Passive Acoustic Monitoring (PAM) methods that are well established in marine systems to freshwater systems to map spatial and temporal patterns of behaviors associated with fish sounds as well as noise impacts on them. Unfortunately, these efforts are greatly hampered by a critical lack of data on the sources of sounds that make up the soundscape of freshwater habitats. A rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
(70 reference statements)
3
25
0
Order By: Relevance
“…While ecoacoustic analysis using indices or spectrograms is still feasible (Gottesman et al, ; Linke, Decker, Gifford & Desjonquères, ), even when not all sounds are resolved, interpretation can sometimes be difficult. We, therefore, concur with Rountree, Bolgan and Juanes (): in many cases, it is imperative to know and catalogue the source of the sounds. Example applications that cannot work without detailed characterisations are monitoring endangered species or tracking invasion front by soniferous species such as tilapia or brown bullhead catfish.…”
Section: Characterising Sounds and Linking Occurrences To Organisms Asupporting
confidence: 68%
“…While ecoacoustic analysis using indices or spectrograms is still feasible (Gottesman et al, ; Linke, Decker, Gifford & Desjonquères, ), even when not all sounds are resolved, interpretation can sometimes be difficult. We, therefore, concur with Rountree, Bolgan and Juanes (): in many cases, it is imperative to know and catalogue the source of the sounds. Example applications that cannot work without detailed characterisations are monitoring endangered species or tracking invasion front by soniferous species such as tilapia or brown bullhead catfish.…”
Section: Characterising Sounds and Linking Occurrences To Organisms Asupporting
confidence: 68%
“…Although there has been a dramatic increase in awareness and attention to soundscapes in marine systems in the last decade, and in particular the effects of noise [25], attention has only recently begun to trickle over to freshwater systems. Furthermore, the lack of familiarity with biological sounds in freshwater habitats [8] contributes to their being overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, after long neglect there has been a recent surge in interest in the potential impacts of anthropogenic noise on freshwater ecosystems [37], but efforts to understand such impacts are hampered by the paucity of data on the natural soundscape composition. The paucity of data on the sound production of freshwater fishes was highlighted in our recent review of the literature which found that sounds have been reported in only 87 species in North America and Europe, but detailed descriptions of sound characteristics are known for only 30 species [8].…”
Section: Introductionmentioning
confidence: 99%
“…The most extensive and well known of them is the Macaulay Library hosted at Cornell University. These sound archives are also valuable tools to share species specific sounds; however, too few freshwater sounds are available in existing archives (Linke, Gifford, et al., ; Rountree, Bolgan, & Juanes, ).…”
Section: How To Undertake Pam In Freshwatermentioning
confidence: 99%